2010
DOI: 10.3138/carto.45.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Champlain's Travels: Restorative Techniques for Historical Cartography

Abstract: Samuel de Champlain's travels through what would become New France have been extensively documented and mapped by geographers and historians today. As conventional cartographic depictions of the routes of a European explorer and colonizer, these maps portray the locational details of Champlain's journeys but omit the emotional geographies and the sense of place evoked in his journals, as well as the Indigenous geographies interwoven with Champlain's story. This article suggests techniques for restoring multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 11 publications
0
11
0
2
Order By: Relevance
“…We could thus reflect on how we might have created an improved map that would have better incorporated dreams and dreaming practices. A possible avenue for research might be that suggested by Margaret Pearce and Michael Hermann, that is, to create new narrative and graphic techniques for incorporating Mapuche spiritual and cultural experiences of place into a conventional Western map Pearce and Hermann 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We could thus reflect on how we might have created an improved map that would have better incorporated dreams and dreaming practices. A possible avenue for research might be that suggested by Margaret Pearce and Michael Hermann, that is, to create new narrative and graphic techniques for incorporating Mapuche spiritual and cultural experiences of place into a conventional Western map Pearce and Hermann 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Margaret Pearce and Michael Hermann, who have worked on cartographic depictions of the journeys of European explorers and colonizers in North America, have questioned the presuppositions of rationality and objectivity of conventional Western cartographic representations by experimenting with new narrative and graphic techniques that enable the inclusion of emotional geographies and multiple experiences of place (rather than space) in maps. This approach is innovative in two dimensions because it contributes to the decolonization of historical cartography by giving voice to Indigenous narratives that have traditionally been silenced in Western mapping while opening new research avenues for cartographers to map emotions and affects Pearce and Hermann 2010).…”
Section: Indigenous Cartographic Traditionsmentioning
confidence: 99%
“…First, visual storytelling invites designers to be reflexive about their positionality and subjectivity (Ricker, 2017;Kelly, 2019). Just as data cannot speak for themselves (Gould, 1981), stories cannot tell themselves, and stories that include the designer's voice in the telling can be more compelling and relatable (e.g., Hermann and Pearce, 2010;Pearce and Hermann, 2010). Second, visual storytelling embraces pluralism and varying perspectives (D'Ignazio and Klein, 2016;D'Ignazio and Klein, 2020).…”
Section: Some Common Visual Storytelling Themesmentioning
confidence: 99%
“…In previous work, I transposed narrative techniques from literature and film to the language of the map as a means of re-imagining and reexpressing historical landscapes (Pearce, 2008;Pearce and Hermann, 2010). For the transcultural mapping projects of recent years, I have focused on translation theory (specifically, the balance of domestication and foreignisation in cartographic translation) and semiotics, particularly the denotative and connotative structures of the sign.…”
Section: Introductionmentioning
confidence: 99%